Flexor accessorius longus: A rare variation of the deep extrinsic digital flexors of the leg and its phylogenetic significance - Jaijesh P; Shenoy M; Anuradha L; Chithralekha K (Indian Journal of Plastic Surgery)
Anomalies of the calf muscles are rare. One such anomalous muscle, known as the Muscle Flexor accessorius longus (also named accessorius ad accessorium, accessorius secondus, accessory flexor digitorum longus or pronator pedis) is of morphological significance. When present, this originates in the deep fascia of the tibia or fibula and inserts in the foot either into the flexor digitorum accessorius or into the tendons of the flexor digitorum longus. In this report we present a discussion of the morphological significance and phylogenetic history of one such muscle observed. In this case report we describe an anomalous calf muscle which extends from the popliteal region, runs along the posterior compartment of the leg, reaches the sole and is inserted to the flexor digitorum longus muscle. This kind of muscle variations are considered to be the higher origin of the flexor digitorum accessorius muscle of the sole. Here we discuss the phylogenetic history of this muscle as this muscle variant is present in some primitive mammals, absent in apes and in this particular case appeared as one of the muscles of the flexor compartment of the leg.